No effects of ozonated autohemotherapy on inflammation response in hemodialyzed patients - Leszek Tylicki; Bogdan Biedunkiewicz; Dominik Rachon; Tomasz Nieweglowski; Lukasz Hak; Andrzej Chamienia; Alicja Debska-Slizien; Ewa Aleksandrowicz; Jolanta Mysliwska; Boleslaw Rutkowski (Mediators of Inflammation)
BACKGROUND: Ozone as a strong oxidant may induce an inflammatory response.